Kinds of Improvisation Activity in Music Secondary Schools - Ustinskovs, Jevgeņijs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Pedagogical experience and findings of different scholars testify to the fact that mastering improvisation can be based on essentially different didactic approaches. Therefore, at developing the didactic model of mastering improvisation in music secondary school, a necessity arises to study kinds of improvisation activity and define the more important kinds of improvisation activities for mastering improvisation in music secondary schools. The research method: analysis of literature, analysis of the author’s pedagogical experience.We consider that for mastering improvisation at music school, it is essential to use such kinds of improvisation activities as: rhythmic and rhythmic-melodic improvisation; imagery improvisation; total and partial improvisation; continuous and episodic improvisation; solo and collective improvisation; musical improvisation on various instruments; improvisation in other arts; technology-based improvisation activities.